Therapeutic Role of Sirtuins Targeting Unfolded Protein Response, Coagulation, and Inflammation in Hypoxia-Induced Thrombosis - Sadia, Khan; Ashraf, Mohammad Zahid; Mishra, Aastha (Frontiers in Physiology, 2021)
Thrombosis remains one of the leading causes of morbidity and mortality across the world. Many pathological milieus in the body resulting from multiple risk factors escort thrombosis. Hypoxic condition is one such risk factor that disturbs the integrity of endothelial cells to cause an imbalance between anticoagulant and procoagulant proteins. Hypoxia generates reactive oxygen species (ROS) and triggers inflammatory pathways to augment the coagulation cascade. Hypoxia in cells also activates unfolded protein response (UPR) signalling pathways in the endoplasmic reticulum (ER), which tries to restore ER homeostasis and function. But the sustained UPR linked with inflammation, generation of ROS and apoptosis stimulates the severity of thrombosis in the body. Sirtuins, a group of seven proteins, play a vast role in bringing down inflammation, oxidative & ER stress and apoptosis. As a result, sirtuins might provide a therapeutic approach towards the treatment or prevention of hypoxia-induced thrombosis. Sirtuins modulate hypoxia-inducible factors (HIFs) and counteract ER stress-induced apoptosis by attenuating protein kinase RNA-like endoplasmic reticulum kinase (PERK) / Eukaryotic translation initiation factor 2α (eIF2α) pathway activation. It prevents ER-stress mediated inflammation by targeting X-Box Binding Protein 1 (XBP1) and inhibiting nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κβ) signalling through deacetylation. Sirtuins also obstruct nucleotide-binding domain, leucine-rich-containing family, pyrin domain containing 3 (NLRP3) inflammasome activation to reduce the expression of several pro-inflammatory molecules. It protects cells against oxidative stress by targeting nuclear factor erythroid 2-related factor 2 (Nrf2), glutathione (GSH), forkhead box O3 (FOXO3), superoxide dismutase (SOD), catalase (CAT), Peroxisome proliferator-activated receptor gamma coactivator 1α (PGC-1α), glucose-6-phosphate dehydrogenase (G6PD), Phosphoglucomutase-2 (PGAM2), NF-κB, to name few. This review, thus, discusses the potential role of sirtuins as a new treatment for hypoxia-induced thrombosis that involves an intersection of UPR and inflammatory pathways in its pathological manifestation.